Biosorbent derived from coffee husk for efficient removal of toxic heavy metals from wastewater. (December 2021) - Quyen, Vu thi; Pham, Thi- Huong; Kim, Jitae; Thanh, Dang My; Thang, Phan Quang; Van Le, Quyet; Jung, Sung Hoon; Kim, TaeYoung
Abstract: In this study, we investigated the feasibility on the utilization of coffee husk as biosorbents for the removal of heavy metal ions such as Pb 2+ and Cd 2+ from wastewater. Biochar was produced from coffee wastes and modified with sodium hydroxide to create functional groups on the surface and increase the specificic surface area. The resultant products were characterized by using various analytical methods such as scanning electron microscopy, specific area, surface functional group and zeta potential analysis. The as-prepared materials were employed as adsorbent to remove Pb 2+ and Cd 2+ ions from wastewater. The maximum sorption capacities of biosorbents were measured to be 116.3 and 139.5 mg g −1 for Cd 2+ and Pb 2+, respectively, which is comparable to the conventional adsorbents. Kinetic studies showed that the sorption of Pb 2+ and Cd 2+ on biosorbents can be described by the Freundlich isotherm and second-order kinetic model. The coffee husk-derived biosorbent was capable of removing 89.6% of Pb 2+ and 81.5% Cd 2+ ions from wastewater, and therefore can be considered as low-cost and efficient adsorbent to remove heavy metal ions from wastewater. Graphical abstract: Image 1 Highlights: Low-cost biosorbent was prepared from coffee husk biomass for removal of heavy metals. Maximum adsorption capacities of Cd and Pb were 116.3 and 139.5 mg g −1, respectively. 81.5% of Cd and 89.6% of Pb was removed from wastewater by using coffee biochar.